Perencanaan Struktur Kantor Pabrik Pakan Udang - Dicky Rizaldo Rengga Ardana (Fakultas Teknik, 2025)
Sampah rumah tangga menjadi salah satu permasalahaan yang sulit teratasi. Hal tersebut terbukti masih banyak This structural planning study for a shrimp feed factory office building aims to enhance the author's knowledge in Civil Engineering, particularly in building design. The objectives include developing a comprehensive office building plan and applying SAP2000 and Building Information Modeling (BIM) Level 2 software to visualize structural elements in 2D and 3D, perform quantity take-off, and conduct clash detection. The structural system employed is the Special Moment Resisting Frame System (SMRFS), designed to withstand seismic loads through the strong column–weak beam concept, allowing significant plastic deformations without loss of structural strength. Structural analysis is conducted using the Dynamic Response Spectrum Method, enabling evaluation of the structure's response to seismic loads based on the design response spectrum. The building is planned with dimensions of 25 x 13 meters, with space requirements and user capacity determined to support the company's operations. Structural analysis involves appropriate loading to design cross-sections and reinforcement, followed by checks to ensure structural safety. The analysis results indicate that the planned structure is safe. SAP2000 software is utilized for structural modeling and analysis by inputting loads and checking preliminary cross-section designs. BIM is used for final modeling of each structural element, clash detection, and quantity take-off. No clashes were found in this planning, and the total volume of concrete material for all elements is 291.26 m³. The required reinforcement amounts are: D16 at 13,234.81 kg, D13 at 3,988.08 kg, D12 at 3,508.6 kg, D10 at 32,630.52 kg, and Ø10 at 7,928.41 kg. These results can serve as a reference for preparing the Budget Plan (RAB).
Reaploud Repository February_Hasyim
Keywords: Structural planning; SMRFS; Dynamic Response Spectrum Method; SAP2000; BIM Level 2; clash detection; quantity take-of